Screening and preclinical assessment of novel Mycobacterium tuberculosis recombinant antigens based tuberculin skin testing - Ou, Xichao; Liu, Eryong; Rashid, Faiqa; Pei, Shaojun; Zhang, Guoqin; Anthony, Richard; Xing, Ruida; Huang, Fei; Xia, Hui; Zheng, Yang; Song, Yuanyuan; Zhou, Yang; et al. (Frontiers in Immunology, 2025)
IntroductionA new class of Mycobacterium tuberculosis (MTB) antigen-based skin tests was recommended by WHO for the diagnosis of TB infection. However, their performance in some settings remains suboptimal. Our study focused on screening novel MTB recombinant antigens for skin tests and evaluating their preclinical efficacy for TB infection detection.MethodsWe constructed Escherichia coli BL21 expression vectors to produce a series of recombinant MTB antigens. We assessed their ability to detect tuberculosis infection through skin tests. Model animals sensitized with MTB and BCG were treated with a total of 24 MTB recombinant antigens.ResultsOut of 24 tested recombinant MTB antigens, only three (E-M, E-C-M, and E-7.7-C) met the criteria for skin test reaction interpretation for preclinical trials. Among these, the mean values of skin reaction from E-M were found to be comparable to EC (P>0.05), with no cross-reaction with BCG. Additionally, E-M exhibited a strong safety preclinical profile with no significant abnormalities in physiological, biochemical, or histopathological assessments, supporting its suitability for clinical evaluation. It also displayed high specificity by differentiating MTB infection from BCG vaccination and NTM infection, with no cross-reactivity observed in sensitized guinea pigs.DiscussionOur results indicate that the E-M recombinant antigen possesses promising characteristics for the detection of tuberculosis infection, demonstrating good safety and efficacy at the preclinical level. Further clinical trials are required to assess its clinical safety, efficacy, and feasibility.